Black phosphorus, an advanced versatile nanoparticles of antitumor, antibacterial and bone regeneration for OS therapy - Lihui Sun; Yu Han; Yao Zhao; Jing Cui; Zhiguo Bi; Shiyu Liao; Zheru Ma; Fengxiang Lou; Chunsheng Xiao; Wei Feng; Jianguo Liu; Bo Cai; et al. (Frontiers Media S.A., 2024)
Osteosarcoma (OS) is the most common primary malignant bone tumor. In the clinic, usual strategies for OS treatment include surgery, chemotherapy, and radiation. However, all of these therapies have complications that cannot be ignored. Therefore, the search for better OS treatments is urgent. Black phosphorus (BP), a rising star of 2D inorganic nanoparticles, has shown excellent results in OS therapy due to its outstanding photothermal, photodynamic, biodegradable and biocompatible properties. This review aims to present current advances in the use of BP nanoparticles in OS therapy, including the synthesis of BP nanoparticles, properties of BP nanoparticles, types of BP nanoparticles, and modification strategies for BP nanoparticles. In addition, we have discussed comprehensively the application of BP in OS therapy, including single, dual, and multimodal synergistic OS therapies, as well as studies about bone regeneration and antibacterial properties. Finally, we have summarized the conclusions, limitations and perspectives of BP nanoparticles for OS therapy.